Peningkatan Kualitas Pembelajaran Vokal Melalui Pendampingan Penyusunan Buku Kurikulum pada Kursus Musik Griya Svara - Sukma Asmarani, Kidung; Purnamasari, Dwi; Salafiyah, Nafik (PELITA NUSA TENGGARA, 2025)
Griya Svara Banjarnegara is a music course institution with a strong commitment to providing high-quality music education. However, in practice, it faces several challenges, including a weak curriculum and the absence of well-structured teaching materials. This study aims to improve the quality of vocal learning at Griya Svara Music Course through assistance in developing a curriculum book. The method employed is participatory-based mentoring, involving instructors, managers, and music practitioners in designing the curriculum structure, basic competencies, teaching materials, and learning evaluation. The results show that this mentoring process produced a curriculum book containing structured learning from beginner to advanced levels, while also enhancing instructors’ teaching skills. The implementation of this curriculum has proven to clarify learning objectives, simplify the evaluation process, and increase students’ learning motivation. With the availability of the curriculum book, vocal learning at Griya Svara has become more systematic, measurable, and aligned with the needs of the music industry.